Identification of Selective Agonists and Positive Allosteric Modulators for µ- and δ-Opioid Receptors from a Single High-Throughput Screen. (October 2014) - Burford, Neil T.; Wehrman, Tom; Bassoni, Daniel; O'Connell, Jonathan; Banks, Martyn; Zhang, Litao; Alt, Andrew
Hetero-oligomeric complexes of G protein–coupled receptors (GPCRs) may represent novel therapeutic targets exhibiting different pharmacology and tissue- or cell-specific site of action compared with receptor monomers or homo-oligomers. An ideal tool for validating this concept pharmacologically would be a hetero-oligomer selective ligand. We set out to develop and execute a 1536-well high-throughput screen of over 1 million compounds to detect potential hetero-oligomer selective ligands using a β-arrestin recruitment assay in U2OS cells coexpressing recombinant µ- and δ-opioid receptors. Hetero-oligomer selective ligands may bind to orthosteric or allosteric sites, and we might anticipate that the formation of hetero-oligomers may provide novel allosteric binding pockets for ligand binding. Therefore, our goal was to execute the screen in such a way as to identify positive allosteric modulators (PAMs) as well as agonists for µ, δ, and hetero-oligomeric receptors. While no hetero-oligomer selective ligands were identified (based on our selection criteria), this single screen did identify numerous µ- and δ-selective agonists and PAMs as well as nonselective agonists and PAMs. To our knowledge, these are the first µ- and δ-opioid receptor PAMs described in the literature.